Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4997/jrcpe.2015.310
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic criteria of pityriasis rosea and Gianotti-Crosti syndrome – a protocol to establish diagnostic criteria of skin diseases

Abstract: We established and validated diagnostic criteria for pityriasis rosea and Gianotti-Crosti syndrome. In this paper, we compare and contrast both diagnostic criteria to formulate a protocol in establishing diagnostic criteria for other dermatological diseases. The diagnostic criteria are similar in employing clear dividing lines and conjunctions ('and/or') to assure high reliability. Both sets of criteria should be applicable for all ethnic groups. Spontaneous remission is not included, so diagnosis is not delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Patient clustering and epidemics can now be detected by various analyses. 8 , 9 Softwares are available for systematic reviews and meta-analyses. 10 Various plots facilitate meta-analyses 11 and the estimation of publication bias.…”
Section: Introductionmentioning
confidence: 99%
“…Patient clustering and epidemics can now be detected by various analyses. 8 , 9 Softwares are available for systematic reviews and meta-analyses. 10 Various plots facilitate meta-analyses 11 and the estimation of publication bias.…”
Section: Introductionmentioning
confidence: 99%
“…Our quantitative analyses including sub-group analyses and meta-analyses indicated that the inclusion of ED findings would be helpful for several sub-groups such as children with pityriasis rosea and some variants of pityriasis rosea [15,16]. The sensitivity, specificity, and positive and negative predictive values as a whole were not elevated if ED findings were incorporated as part of the criteria [17].…”
Section: Researchmentioning
confidence: 93%
“…Typical herald patch, peripheral scaling, and asymptomatic lesions in “Christmas tree” pattern or distribution were the essential constituents of such diagnosis. [ 12 13 ]…”
Section: Methodsmentioning
confidence: 99%